(untitled) (Physical Education, Health and Social Sciences, 2026)
This study observes the experiences and challenges faced by secondary school instructors in executing the Single National Curriculum (SNC). With the introduction of SNC directing to categorize learning outcomes and improve the excellence of education, accepting teachers’ perspectives is vital for optimistic curriculum enactment. This qualitative study employed a phenomenological design, involving semi-structured interviews and classroom observations of 15 secondary school teachers from private schools. The findings reveal that teachers actively acclimatize their lesson plans and employ student-centered teaching approaches, containing group activities and collaborating discussions, to bring into line with SNC intentions. However, some challenges were recognized, including inadequate teaching resources, dissimilar student abilities, large class sizes, and inadequate professional preparation. The study also acmes the critical role of official support, professional development, and association among teachers in smoothing effective curriculum implementation. Based on these findings, endorsements include enhancing teacher training programs, improving access to teaching resources, supporting teachers in managing diverse classrooms, solidification administrative and peer support, and observing curriculum implementation to ensure quality and equity in education. The study contributes to understanding the useful realities of SNC implementation and provides visions for policymakers, school managers, and teachers to develop curriculum delivery at the secondary level.